Effect of pt incorporation in LaBO3 (B = Mn, Fe, Co) perovskites on water gas shift activity - Rajesh, Thattarathody; Upadhyay, Anuj; Sinha, Anil K.; Deb, Sudip K.; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt incorporated perovskites LaBO3 (B = Mn, Co, Fe) were synthesised and characterised to understand the charge state of Pt in these materials. At the temperature range used in this study, Pt could be stabilised in ionic form in Co and Fe perovskites but not in LaMnO3. Consequent to incorporation of Pt in +2 and +4 oxidation states, reduction in B site ion charge state occurred, enhancing oxygen vacancies. Pt doped Co and Fe perovskites showed high activity for CO conversion under water gas shift conditions but the activity characteristics were found to be different for the two catalysts; LaCo1-xPtxO3-delta showed methanation whereas the Fe counterpart was active in water gas shift reaction. It was also observed that methanation could be decreased and water gas shift enhanced in case of Pt doped Co perovskite when compared to Pt impregnated perovskite or mixed oxides. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Methanation; Perovskites; Pt doping; Water gas shift reaction; XANES

Resistance to ionic pt insertion in oxygen excess LaMnO3 perovskite lattices and its effect in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt doped and impregnated LaMnO3 perovskites are synthesized at different temperatures and Pt and Mn states are compared in an attempt to get insight into extent of lattice incorporation of Pt in perovskite. Various characterization studies indicate that oxygen excess system like LaMnO3 presents substantial resistance to B site doping with Pt. This behavior is different from other oxygen deficient perovskites like LaCoO3 and LaFeO3 in which lattice incorporation stabilizes the active species against sintering. Water gas shift reaction was used as a probe reaction to understand the effect of this difference in the activity. In case of LaMnO3, failure in lattice substitution leads to sintering and deactivation at high synthesis temperatures (>= 700 degrees C) in both impregnated and doped samples. In doped samples, however, a strong interaction of Pt species with a persistent amorphous phase prevents sintering at lower synthesis temperature thereby enhancing the activity when compared to impregnated sample. The study reveals a possible mechanism in which only Pt(0) species is active with perovskite playing a minimal role in this system due to the resistance to lattice incorporation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Oxygen excess; Perovskites; Water gas shift reaction; XPS; XRD